1991
DOI: 10.1104/pp.97.1.420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Photorespiratory Enzyme Activity in Response to Limiting CO2 in Chlamydomonas reinhardtii

Abstract: The activity of two photorespiratory enzymes, phosphoglycolate phosphatase (PGPase) and glycolate dehydrogenase (glycolate DH), changes when C02-enriched wild-type (WT) Chlamydomonas reinhardtii cells are transferred to air levels of CO2. Adaptation to air levels of C02 by Chiamydomonas involves induction of a C02-concentrating mechanism (CCM) which increases the internal inorganic carbon concentration and suppresses oxygenase activity of ribulose-1,5-bisphosphate carboxylase/oxygenase. PGPase in cell extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 25 publications
7
36
1
Order By: Relevance
“…3C). Ser is an essential amino acid and a metabolite in the photorespiratory pathway, which is known to be up-regulated upon induction of the CCM (Marek and Spalding, 1991;Tural and Moroney, 2005). Malate is a central metabolite in many different metabolic pathways (e.g.…”
Section: Lowering Of the Co 2 Concentration Causes A Transient Metabomentioning
confidence: 99%
See 1 more Smart Citation
“…3C). Ser is an essential amino acid and a metabolite in the photorespiratory pathway, which is known to be up-regulated upon induction of the CCM (Marek and Spalding, 1991;Tural and Moroney, 2005). Malate is a central metabolite in many different metabolic pathways (e.g.…”
Section: Lowering Of the Co 2 Concentration Causes A Transient Metabomentioning
confidence: 99%
“…Many genes coding for enzymes of the photorespiratory pathway are up-regulated (Marek and Spalding, 1991;Miura et al, 2002Miura et al, , 2004 within 20 min and show a transient expression pattern (Tural and Moroney, 2005;Yamano et al, 2008). A decline in starch content is also detectable within 30 min after transfer to low CO 2 (Kuchitsu et al, 1988).…”
mentioning
confidence: 99%
“…Isolation and characterization of the C. reinhardtii mutants, ca-1 and pmp-1, demonstrated the requirement for active transport and accumulation of C i (Badger et al, 1980;Spalding et al, 1983b) and for a thylakoid lumen CA (Spalding et al, 1983a;Funke et al, 1997;Karlsson et al, 1998) for function of the CCM. Another C. reinhardtii HCR mutant, cia-5, exhibits no apparent low-CO 2 acclimation responses, such as induction of CCM, up-regulation of low CO 2 -inducible polypeptides, up-regulation of photorespiratory enzymes, or down-regulation of Rubisco biosynthesis (Moroney et al, 1989;Marek and Spalding, 1991;Spalding et al, 1991;Burow et al, 1996). This mutant is thought to be defective in the signal transduction pathway for acclimation to limiting CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Modification of several sites within the genomic region of rbc in Synechococcus PCC 7942, including rbcS, resulted in high C02-requiring mutants (9,13,20). It was, therefore, suggested that this region contains a cluster of genes, the products of which are involved in various functions of the Ci-concentrating mechanism and, hence, in the ability of cyanobacteria to grow in the presence of low CO2.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these mutants exhibit an apparent photosynthetic affinity approximately 2 orders of magnitude lower than that of high C02-grown wild type (5, 7, 9, 10, 12, 15-17, 19, 22, 25). High C02-requiring mutants in which the photosynthetic characteristics are similar to those observed in wild-type cells grown under high C02 were isolated from Chlamydomonas reinhardtii (13) and Synechococcus sp. PCC 7942 (10).…”
mentioning
confidence: 99%